Environmental Radionuclides in Surface Soils of Vietnam - P.D. Hien; H.T. Hiep; N.H. Quang; T.V. Luyen; N.T. Binh; N.T. Ngo; N. Q. Long; V. T. Bac (The Scientific World Journal)
A database on 238U, 232Th, 40K, and 137Cs in surface soils was established to provide inputs for the assessment of the collective dose to the population of Vietnam and to support soil erosion studies using 137Cs as a tracer. A total of 292 soil samples was taken from undisturbed sites across the territory and the concentrations of radionuclides were determined by gamma spectrometry method. The multiple regression of 137Cs inventories against characteristics of sampling locations allowed us to establish the distribution of 137Cs deposition density and its relationship with latitude and annual rainfall. The 137Cs deposition density increases northward and varies from 178 Bq m–2 to 1,920 Bq m–2. High rainfall areas in the northern and central parts of the country have received considerable 137Cs inputs exceeding 600 Bq m–2, which is the maximum value that can be expected for Vietnam from the UNSCEAR global pattern. The mean activity concentrations of naturally occurring radionuclides 238U, 232Th, and 40K are 45, 59, and 401 Bq kg–1, respectively, which entail an average absorbed dose rate in air of 62 nGy h–1, which is about 7% higher than the world average.